2015
DOI: 10.1111/ajad.12306
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic management of comorbid post-traumatic stress disorder and addictions

Abstract: Comorbid PTSD and SUD amplifies their lethality and treatment complexity. Although they share important neurobiology, these patients uncommonly respond to a single pharmacotherapy such as sertraline or disulfiram and more typically require medication combinations and consideration of the specific type of SUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…Depending on the specific rodent drug self-administration paradigm used, specific features of human drug abuse can be evaluated (Panlilio et al, 2005; Sughondhabirom et al, 2005; Panlilio and Goldberg, 2007). Although it has been established that repeated cocaine consumption triggers long-lasting changes in brain plasticity, which contribute to drug craving during abstinence and might induce relapse into cocaine-seeking behavior, we still have a very limited understanding of the exact molecular changes in the brain, which is reflected by the poor success in developing efficient drugs for cocaine addiction (Shorter et al, 2015; Wolf, 2016). To increase our understanding of the changes taking place in the striatum from the first CSA to chronic CSA through CSA withdrawal, we studied the progression of mGluR 1/5 responses in striatal slices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the specific rodent drug self-administration paradigm used, specific features of human drug abuse can be evaluated (Panlilio et al, 2005; Sughondhabirom et al, 2005; Panlilio and Goldberg, 2007). Although it has been established that repeated cocaine consumption triggers long-lasting changes in brain plasticity, which contribute to drug craving during abstinence and might induce relapse into cocaine-seeking behavior, we still have a very limited understanding of the exact molecular changes in the brain, which is reflected by the poor success in developing efficient drugs for cocaine addiction (Shorter et al, 2015; Wolf, 2016). To increase our understanding of the changes taking place in the striatum from the first CSA to chronic CSA through CSA withdrawal, we studied the progression of mGluR 1/5 responses in striatal slices.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine addiction is a complex multifaceted condition, which thus far has impeded the development of efficient pharmacological treatment options (Shorter et al, 2015; Wolf, 2016). Repeated cocaine consumption decreases expression of metabotropic glutamate 5 receptors (mGluR 5 ) in the striatum, a subcortical region critical in mediating the effects of drugs of abuse (Ghasemzadeh et al, 2009; Knackstedt et al, 2010; Martinez et al, 2014; Milella et al, 2014; Pomierny-Chamiolo et al, 2015; Terbeck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that the lifetime prevalence of any substance-use disorder (SUD) was twice as high in persons with PTSD vs. those not suffering from this disorder (Shorter et al 2015) and that alcohol is the most commonly abused drug in PTSD patients (Jacobsen et al 2001). Indeed, a recent study examined the relationship between the frequency of childhood physical, sexual and emotional abuse and the development of substance use and PTSD in an urban, civilian population.…”
Section: Epidemiology Of Comorbid Ptsd and Audmentioning
confidence: 99%
“…Summarizing this literature can inform researchers and clinicians about effective treatments, future research directions, and may offer insight into underlying mechanisms that can be studied preclinically in a bench to bedside and back approach. While several previous reviews of pharmacologic management have been conducted (Norman et al., ; Ralevski et al., ; Shorter et al., ; Sofuoglu et al., ), this review represents a comprehensive critical review that also extends previous work by including several randomized controlled trials (RCTs) that have been very recently published (Batki et al., ; Hien et al., ; Petrakis et al., ; Simpson et al., ).…”
mentioning
confidence: 92%